Co-designing a cross-sectoral community-based zoonoses surveillance system in the wild meat value chain of Gabon - Natacha Efoua Tomo; Aude Pouliquen; Gilles Aurélien Boupana Mapeyi; Patrice Makouloutou-Nzassi; Berthe-Nadine N’dilimabaka; Barthélémy Ngoubangoye; Serge Ely Dibakou; Roland Fabrice Kassa Kassa; Ivan Cyr Moussadji Kinga; Anicet Mouity Matoumba; Hélène Sisraëlla Lembanaka; Thierry Tsoumbou; et al. (CABI One Health, 2026)
Abstract Background : Approximately 60% of recently emerging infectious diseases are zoonotic, with over 70% originating from wildlife. These diseases have significant public health and economic impacts globally, as exemplified by the Ebola epidemics. Community-based surveillance is increasingly recognized as a corner-stone of early warning and prevention systems of zoonotic spillover. In sub-Saharan Africa, wildlife hunting is a vital livelihood activity for rural communities, positioning hunters as frontline observers of wildlife health and potential early indicators of zoonotic threats. Method : We designed and piloted a community-based zoonoses surveillance system in Ogooué-Lolo, eastern Gabon. The study utilized a participatory co-construction approach aimed at engaging all relevant stakeholders. It proceeded in three steps, namely (1) the assessment of existing actors, resources, and barriers relevant to zoonotic disease surveillance; (2) the co-design process of the pilot surveillance system involving community members and institutional stakeholders; and (3) the implementation of the pilot surveillance system. Results : The assessment phase revealed specific challenges related to zoonoses surveillance among involved actors, including unavailability of local animal health services, limited communication between communities and the administration, and limited knowledge of zoonotic risks and capacity to recognize disease suspicions among communities. A One Health approach relying on the collaboration of different sectors (public health, agriculture, and environmental services) was adopted in response, a research institute being responsible for training local actors in disease suspicion recognition and in conducting investigations and laboratory analyses. The pilot surveillance system successfully detected and managed 10 disease suspicions, demonstrating its operational feasibility. Discussion : We demonstrate the feasibility of early warning zoonotic disease surveillance in the challenging context of wild meat systems of Central Africa, using a community-based One Health approach. Further investment in community training, animal health expertise, and financial and material resources is needed to ensure sustainability and scalability of the system. Continued engagement of stakeholders at all levels will be critical to the long-term success of this One Health surveillance model. One Health impact statement Early detection of zoonotic diseases at the wildlife-domestic animal-human interface presents a significant global health challenge. Our study demonstrates the feasibility of establishing a community-based, cross-sectoral surveillance system tailored to the wild meat value chain, where hunters in remote areas serve as primary observers of unusual animal morbidity and mortality. Through the application of participatory methods, we identified key actors, available resources, and barriers to effective surveillance and co-designed a system that integrates hunter communities, government services in the three key One Health sectors, and research institutions. This inclusive process enhanced the acceptance and operationalization of the system. The approach offers a scalable model for One Health surveillance in similar high-risk contexts across Central Africa and beyond.